PENGARUH METODE PENGAJARAN TERHADAP MOTIVASI BELAJAR MAHASISWA ANGKATAN 2017 FIKOM UPDM (B) - Nunuk Prihatiningsih (Jurnal Pustaka Komunikasi, 2019)
This study aims to determine the 2017 UPDM FIKOM Student assessment (B), regarding 1) teaching methods carried out by the Lecturer; 2) Student motivation to learn; 3) the influence of the teaching method on student learning motivation The population of this study were UPDM FIKOM students (B) in 2017 numbering 188 students, the research paradigm using the positivism paradigm, the research approach using a quantitative approach and using survey methods data analysis techniques using linear regression analysis simple to know the magnitude of influence. Simple liner regression is based on functional and causal relationships of one independent variable with one dependent variable.The results showed that there were influences of Teaching Methods on Student Learning Motivation. The results of this study also assessed that the teaching method used by lecturers was good.